The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s12126-010-9076-x
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Disruptive Innovation Framework to the Silver Market

Abstract: Despite the increased attention that the topic of aging and technology is receiving from academia, policy and business practice, both conceptual and empirical research in this area is still scarce. Particularly, there seems to be a dearth of applications of well-grounded and established frameworks from the field of innovation and technology management to the case of older consumers and the "silver market." Through an approach that combines conceptual development with explorative empirical research using the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…For example, in Japan, the idea of using robots as household helpers for older adults dates back to the 1980s, and regular use of robot pets in long-term care settings emerged in the early 1990s (Wagner, 2009). Notably, Asian researchers have emphasized robot technology as providing solutions rather than merely enabling assessment, and they recognized early on the market potential of these strategies for supporting older adults (Kohlbacher & Hang, 2011).…”
Section: A Brief History Of Research On Aging and Technologymentioning
confidence: 99%
“…For example, in Japan, the idea of using robots as household helpers for older adults dates back to the 1980s, and regular use of robot pets in long-term care settings emerged in the early 1990s (Wagner, 2009). Notably, Asian researchers have emphasized robot technology as providing solutions rather than merely enabling assessment, and they recognized early on the market potential of these strategies for supporting older adults (Kohlbacher & Hang, 2011).…”
Section: A Brief History Of Research On Aging and Technologymentioning
confidence: 99%
“…Hence, rejuvenation made e-bikes simpler and cheaper. This is important as it runs counter to the common assumption that technology needs to be simpler and cheaper to reach out to older persons (Fisk et al 2009; Kohlbacher and Hang 2011). Our analysis of the adoption of e-bikes thus highlights the age-based assumptions and biases that underlie the development of technologies for older people and shows that contrary to commonly held beliefs, older people––even when they are in their fourth age––can act as innovators and participants in design processes.…”
Section: Conclusion: Rejuvenating Designmentioning
confidence: 94%
“…Studies have revealed that mature people are extra resilient while adopting technology because of many factors, such as difficulty in understanding, usability, and the perceived complexity of new technology (Kohlbacher & Hang, 2011); however, developing products and technologies for older users is not an easy task Compagna & Kohlbacher, 2015). Surely, technology has brought benefits to many aspects of aged people's lives and will definitely bring positive changes to their QoL (Kohlbacher & Hang, 2011). Sirgy (1986) defined QoL as the satisfaction of the hierarchical need of the followers of a specified culture, and satisfaction shows the QoL of the aggregate members of a society.…”
Section: Older Consumers and Aging Populationmentioning
confidence: 99%